Sexual Orientation in Counsellor Supervision - Allan, Robert; Estrada, Diane; Poulsen, Shruti Singh; Nwosu, LaTrease L. (Canadian Journal of Counselling and Psychotherapy, 2017)
Little research exists about whether sexual orientation is addressed in counsellor supervision. This study examined supervisees’ and supervisors’ perceptions of how knowledge, awareness, and skills related to lesbian, gay, or bisexual issues were addressed in supervision. Results indicated there was no correlation between supervisors’ own sexual orientation identity and their perception of exploration of awareness, knowledge, and development of skills as related to issues of sexual orientation in clinical work. This study did find a significant difference between supervisors’ and supervisees’ perceptions of supervisors’ explorations related to awareness of issues of sexual orientation in counselling. Implications for counsellor supervision are discussed.